Decision to Practice Agroforestry among Farmers in Ogun State of Nigeria: Implication for Climate Change Mitigation - Oyewole, Samuel Olusola; Oyewole, Adekemi Lizzie; Isola, Bose Folashade; Ofordu, Chinyere Salome (Journal of Forests, 2022)
Mitigating climate change through carbon sequestration centered on the availability of trees. This study evaluates farmers’ specific socioeconomic features that affect decision to practice agroforestry for the purpose of climate change mitigation among smallholder farmers in Ogun State of Nigeria. The study adopted a multi-stage sampling technique in the selection of was n of 196 farmers. Primary data were collected with the application of structured questionnaires. The collected data were analysed using descriptive statistics and logit regression analysis. Based on the findings of the study, male farmers were the majority with mean age of 36 years cultivating an average farm size of 7.1hectares. Only 10.20% had no formal education. The average experience in farm production was 14 years More than half 59.69% of the farmers acquired their land through purchase. Majority (70.41%) of the farmers were practicing agroforestry. This is a good indication for climate change mitigation and environmental resource management. Factors influencing agroforestry practice among farmers were farm size, experience in farming and income received from farm business. The study recommends a policy strategy that will facilitate famers’ access to farmland with long tenure security.